2015
DOI: 10.3389/fmicb.2015.00622
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport phosphorylation in rumen butyrivibrios: unprecedented ATP yield for glucose fermentation to butyrate

Abstract: From a genomic analysis of rumen butyrivibrios (Butyrivibrio and Pseudobutyrivibrio sp.), we have re-evaluated the contribution of electron transport phosphorylation (ETP) to ATP formation in this group. This group is unique in that most (76%) genomes were predicted to possess genes for both Ech and Rnf transmembrane ion pumps. These pumps act in concert with the NifJ and Bcd-Etf to form a electrochemical potential (ΔμH+ and ΔμNa+), which drives ATP synthesis by ETP. Of the 62 total butyrivibrio genomes curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 63 publications
6
55
1
1
Order By: Relevance
“…S2A). However, as in a previous study (Hackmann and Firkins, ), we found that some Butyrivibrio and Pseudobutyrivibrio ( n = 3) encode an atypical pathway for forming butyrate (Supporting Information Fig. S2B).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…S2A). However, as in a previous study (Hackmann and Firkins, ), we found that some Butyrivibrio and Pseudobutyrivibrio ( n = 3) encode an atypical pathway for forming butyrate (Supporting Information Fig. S2B).…”
Section: Resultssupporting
confidence: 86%
“…A previous study from our group found an atypical pathway for butyrate formation in most butyrivibrios ( Butyrivibrio and Pseudobutyrivibrio spp.) (Hackmann and Firkins, ). Specifically, the pathway involves the ion pump Ech hydrogenase, which together with Rnf generates an electrochemical potential and conserves energy.…”
Section: Discussionmentioning
confidence: 99%
“…Among bacteria genera or species that were studied in several experiments, Fibrobacter and Ruminococcus were negatively affected in most cases, but the effects on Butyrivibrio and Prevotella were highly variable. These latter genera comprise many species with somewhat different functions, different metabolic pathways (Hackmann and Firkins ) and different sensitivities to LA in cultures (Maia et al . ).…”
Section: Dietary Fat Shapes Rumen Microbiotamentioning
confidence: 99%
“…A specific effect of the cis double‐bonds could explain why most known biohydrogenating bacteria produce trans‐ C18:1, but do not further reduce it to stearic acid (see below). Hackmann and Firkins () reported that B. fibrisolvens could be less sensitive to LA than B. hungatei and Butyrivibrio proteoclasticus because its membrane has a lower fluidity due to more palmitic acid and less branched‐chain FA.…”
Section: Dietary Fat Shapes Rumen Microbiotamentioning
confidence: 99%
“…Through aerobic oxidation, this stored energy can be made readily available to the host for cellular growth and maintenance. During anaerobic fermentation, the coenzyme NAD + is reduced to NADH/H + through a process of substrate linked phosphorylation (Hackmann and Firkins, 2015). For fermentation to continue, NAD + needs to be regenerated (oxidised) by NAD-linked hydrogenases, which are only thermodynamically favourable at low partial pressures of hydrogen.…”
Section: Rumen Fermentationmentioning
confidence: 99%